Aspen Plus process-simulation model: Producing biogas from VOC emissions in an anaerobic bioscrubber. (1st May 2018) - Bravo, D.; Álvarez-Hornos, F.J.; Penya-roja, J.M.; San-Valero, P.; Gabaldón, C.
Abstract: A process-simulation model for a novel process consisted of an anaerobic bioscrubber was developed in Aspen Plus ® . A novel approach was performed to implement the anaerobic reactor in the simulation, enabling it to be connected to the scrubber. The model was calibrated and validated using data from an industrial prototype that converted air emissions polluted with volatile organic compounds with an average daily concentration of 1129 mgC Nm −3 into bioenergy for more than one year. The scrubber, which showed a removal efficiency within 83–93%, was successfully predicted with an average absolute relative error of 5.2 ± 0.08% using an average height-to-theoretical-plate value of 1.05 ± 0.08 m and 1.37 ± 0.11 m for each of the two commercial packing materials used, respectively. The anaerobic reactor, which treated up to 24 kg of chemical oxygen demand m −3 d −1 with efficiencies of about 93%, was accurately simulated, both in effluent-stream characteristics and in the biogas stream. For example, the average absolute error between the experimental biogas production and the model values was 19.6 ± 18.9%. The model proved its capability as a predictive tool and an aid in design, resulting in savings of time and money for practitioners. In addition, the approach proposed can be expanded to other bioprocesses that include unit operations. Graphical abstract: Image 1 Highlights: An Aspen Plus process-simulation model of anaerobic bioscrubber was developed. The anaerobic reactor was implemented using stoichiometric and kinetic reactors. The model was calibrated and validated using data from an industrial prototype. Both units of the process were simulated with a high level of correspondence. The model proved its ability as a predictive tool and an aid in design.